Effect of different phyto additive mixtures on colostrum production, health status, blood indices and hormonal profile of Black Bengal goats at first kidding - SINGH, AMIT KUMAR; Champak Bhakat56@gmail.com; Bed Singh; Muthupalani Karunakaran; Tapas Kumar Dutta (Indian Journal of Dairy Science, 2025)
This study was conducted to investigate the effects of different phyto additive mixture on colostrum production, health status, blood indices and hormonal profile of Black Bengal goats at first kidding. 21 Black Bengal goat (BBG) kids of similar age and body weight were divided equally into three comparable groups viz. Control (No supplementation), T1 and T2 in this study. Two different powders of phyto additive mixtures comprising equal amounts of PAM-1: Curcuma longa & Allium sativum and PAM-2: Curcuma longa & Ocimum sanctum were prepared and supplemented to T1 (PAM-1 @15g/Kg DM conc.) and T2 (PAM-2 @15g/Kg DM conc.) for a period of 10 months. Significant improvement (P0.05) colostrum composition, udder health (pH, EC, MCMT, SCC) and relative immunity of goats at first kidding. There was significant reduction (P